UTILIZATION OF QUIZIZZ PAPER MODE MEDIA AS AN INNOVATION IN PAI LEARNING EVALUATION AT STATE ELEMENTARY SCHOOL 2 BANDA SAKTI - Nurainun; Naili Surayya; Yusnaini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The implementation of Quizizz Paper Mode as an innovative evaluation tool in Islamic Religious Education (PAI) at SD Negeri 2 Banda Sakti was developed to address the need for a more effective, engaging, and learner-friendly assessment technique suitable for elementary school students. This study aims to describe how Quizizz Paper Mode is applied in the PAI evaluation process and to identify its influence on students' motivation and comprehension. The Paper Mode feature was selected because it integrates the advantages of digital assessment with the convenience of QR-code–based access, making it suitable even for students who do not own personal electronic devices. This research employed a qualitative descriptive approach involving PAI teachers and students as participants. Data were gathered through observations, interviews, and documentation throughout the implementation of the media. The findings reveal that Quizizz Paper Mode successfully fosters a more interactive, enjoyable, and non-monotonous evaluation environment. Teachers benefit from simplified scoring procedures, as the system automatically checks responses, reduces the likelihood of errors, and accelerates the analysis of learning outcomes. Moreover, students demonstrated greater engagement due to the appealing presentation of questions and the assessment format that differs from conventional methods. The challenges encountered mainly relate to technical readiness, including internet availability and teachers' initial proficiency in operating the application. Overall, this innovation effectively supports PAI learning evaluation and holds significant potential for further development within elementary education contexts.